Creative cognition: A multidisciplinary and integrative framework of creative thinking - Felix Pinkow (Creativity and Innovation Management, 2022)
Extant research provides vast information on antecedents to creativity. However, creative thinking is oftentimes treated as a black box, requiring input and producing creative output. Cognitive processes occurring during creative thinking tend to be neglected, although they can provide a bridge between the inputs to creativity and the resulting outputs. Literature offers different perspectives on creative thinking processes, such as the separation of divergent and convergent thinking, different stages of creativity or the concept of creative cognition. This variety of concepts underlying creativity has led to confusion and misinterpretations of some concepts. Moreover, the overemphasis on creative outcomes and divergent thinking has resulted in a neglect of a more comprehensive view on cognitive dimensions of creativity. Through reviewing and synthesizing multidisciplinary literature on creativity, an integrative framework is developed positioning cognitive elements of creativity within a system including organizational antecedents to creativity and creative outcomes. The framework seeks to offer pathways to increasingly incorporate the concept of creative cognition into future research. Suggesting different forms of creative cognition that individuals engage in during creative thought, this theoretical work further offers a theoretical development of creativity concepts that intends to inspire future research designs and facilitates cross-disciplinary knowledge transfer.
Keywords: 330; cognitive processes; conceptual framework; creative cognition; creativity; divergent and convergent thinking; idea generation; literature review